PEMANFAATAN MEDIA AUDIO VISUAL UNTUK MEMBENTUK PERILAKU HIDUP BERSIH DAN SEHAT PADA MASA PANDEMI COVID-19 - Adilah Adiyani; Yohana Sumiyati; Taryatman Taryatman (Universitas Sarjanawiyata Tamansiswa, 2022)
This qualitative study aimed to develop personal hygiene and a healthy lifestyle using audiovisual media for elementary students in SD N Tegalrejo. The primary data of this research were The Headmaster, Teachers, also the Forth until Six Graders of SD Tegalrejo. The data collection approaches used in this study were observation, interview, and documentation. In line with that, the researcher employed Miles and Huberman's data analysis technique, which consists of three techniques namely data reduction, data display, and conclusion drawing. In addition, the researcher applied triangulation techniques to examine the validity of the data. The findings of this research revealed that 1) educational video about the importance of health and hygiene was used in SD N Tegalrejo, 2) video was the most effective audiovisual media due to its ease of access, application, and energy and time savings, and 3) the problem with using audiovisual media was the unstable connection and electrical blackout. To summarize, teachers have another option for getting students adapted to personal hygiene and a healthy lifestyle, such as teaching students directly through offline learning, as well as guiding students to always practice hygiene and a healthy lifestyle at school to get them used to it.